A Systematic Review of Financial Intermediaries Research - Daniel Idoko Anyebe; Umar Mustapha Zubairu; Onuh O.D (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2021)
The purpose of this study is to conduct a systematic review on Financial Intermediaries (FI) with a view to review extant discourses, identify gaps and provide directions for future research in this area. The Systematic Assessment Quantitative Technique (SQAT) developed by Australian researchers Catherine Pickering and Jason Anthony Bryn in (2013), was used to identify and review 43 peer- reviewed Financial Intermediaries (FI) articles from ten high quality academic databases. The primary focus of FI articles in this review were on nine themes and two theories were predominant. The various themes developed from literatures were discussed. The findings of this study would look to guide policy planners and managers on the integral role of financial intermediaries in their daily activities stressing how its overarching function cuts across all facets our financial lives.Keywords:  Financial intermediaries, SQAT, Panel data, Risk management https://doi.org/10.21632/irjbs.14.1.69-84